(untitled) (Islas, 2022)
ABSTRACT: Introduction: The general objective of this work is to characterize the scientific language of the students of Bachelor’s Degree in Chemistry of the Universidad Central «Marta Abreu» de Las Villas. In the 2018-2019 academic year, a diagnosis was made to the fourth year students of the Bachelor’s Degree in Chemistry, determined by the need of the career collective and the year collective and in which some deficiencies related to the use of scientific language were evidenced. Methods: Theoretical and empirical methods were used, by means of which the authors determined existing regularities in the use of the language of science by these students. Results: The main contributions of the work are directed to the generalization of the results of the doctoral thesis The development of oral scientific communication of students of Veterinary Medicine and Zootechnics. This article is derived from the results obtained in the diploma work, Study of the scientific language of the students of Bachelor’s Degree in Chemistry, defended in 2019. Conclusions: The authors will continue to work in this important field of knowledge, since it is one of the prioritized objectives within the study of the mother tongue in Cuba and in the world.